Inhibitory Power of Jatropha (Jatropha curcas L.) Leaf Sap against Streptococcus mutans in Dental and Oral Care in Adults and Elderly - Bahtiar Bahtiar; Nur Aita Akbar; Sulaeha Sulaeha (Alliance oh Health Activists (AloHA), 2024)
Caries is one of the main problems of dental and oral health in adults and the elderly. Treatment of caries in adults and the elderly can be done using natural ingredients that contain anti-bacterial properties against streptococcus mutans bacteria, including Jatropha curcas L. This study aims to determine the effectiveness of Jatropha leaves as an inhibitor of Streptococcus mutans in dental and oral care in adults and the elderly. This study is a narrative review. Information is obtained from various scientific sources in the form of books, articles and other scientific sources. Based on the results of the narrative review above, it can be concluded that the inhibition of jatropha leaf latex (Jatropha curcas L.) against Streptococcus mutans is effective. Keywords: Jatropha curcas L.; Streptococcus mutans; caries; adults; elderly